The Role of Problem-Based Learning in Developing Science Literacy and 21st-Century Skills in High School Students: A Meta-Analysis - Aripin, Nurul; Mufit, Fatni; Lufri, Lufri; Andromeda, Andromeda; Festiyed, Festiyed (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
This study aims to analyse the role of the Problem-Based Learning learning model in developing science literacy and 21st-century skills in science learning for students from junior high to high school levels. This study uses a quantitative model with a meta-analysis method. The source of research data was obtained from the analysis of national and international articles indexed by SINTA, Google Scholar, Eric, and Scopus. The articles sampled were national and international articles published between 2020 and 2024, with a total of 36 articles. Sample selection was carried out through searches on Google Scholar, Eric Journal, and Scopus using the Publish or Perish application and purposive sampling techniques. The research sample was selected through a purposive sampling technique, with a focus on an article that discusses the role of the Problem-Based Learning learning model in developing science literacy and 21st-century skills in science learning for junior and senior high school students. Data analysis was carried out using Microsoft Excel software and JASP 0.18.2.0. The data produced shows that the average score of science literacy and skills in the 21st century increased. The results of the study prove that Problem-Based Learning (PBL) is very effective in developing science literacy and 21st-century skills in science learning in high school students. Thus, meta-analysis research makes the problem-based learning model an innovative learning model to support educational transformation in developing science literacy and 21st-century skills in high school students.